2011
DOI: 10.1107/s1600536811024597
|View full text |Cite
|
Sign up to set email alerts
|

N-(3-Chloro-4-fluorophenyl)-2-(naphthalen-1-yl)acetamide

Abstract: In the title compound, C18H13ClFNO, the dihedral angle between the mean planes of the chloro- and fluoro-substituted benzene ring and the naphthalene ring system is 60.5 (8)°. In the crystal, mol­ecules are linked by N—H⋯O hydrogen bonds, forming a zigzag chain along [101].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Compounds (VIII) and (IX) crystallize in the space groups P2 1 /c and Pbca, respectively, and, whereas in (VIII) molecules related by translation are linked into simple C(4) chains by N-HÁ Á ÁO hydrogen bonds, in (IX) molecules related by a b-glide plane are linked by N-HÁ Á ÁO hydrogen bonds modestly reinforced by C-HÁ Á ÁO hydrogen bonds to form a C(4)C(4)[R 1 2 (6)] chain of rings. In each of compounds (X) (Praveen et al, 2011) planes, respectively, are linked by N-HÁ Á ÁO hydrogen bonds to form C(4) chains running parallel to [101] and [001] respectively. In addition, there are two aromaticstacking interactions in each structure, although these were not mentioned in the original structure reports.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Compounds (VIII) and (IX) crystallize in the space groups P2 1 /c and Pbca, respectively, and, whereas in (VIII) molecules related by translation are linked into simple C(4) chains by N-HÁ Á ÁO hydrogen bonds, in (IX) molecules related by a b-glide plane are linked by N-HÁ Á ÁO hydrogen bonds modestly reinforced by C-HÁ Á ÁO hydrogen bonds to form a C(4)C(4)[R 1 2 (6)] chain of rings. In each of compounds (X) (Praveen et al, 2011) planes, respectively, are linked by N-HÁ Á ÁO hydrogen bonds to form C(4) chains running parallel to [101] and [001] respectively. In addition, there are two aromaticstacking interactions in each structure, although these were not mentioned in the original structure reports.…”
Section: Tablementioning
confidence: 99%
“…stereoview of part of the crystal structure of compound (X), showing the formation of a -stacked sheet of hydrogen-bonded chains parallel to (010). The original atomic coordinates(Praveen et al, 2011) have been used. Hydrogen bonds are shown as dashed lines and, for the sake of clarity, H atoms not involved in the motif shown have been omitted.…”
mentioning
confidence: 99%
“…For studies of amides in therapy, myocardial infarction and ischemic disease, see: Dorsch et al (2002); Wang, Li & Li (2010); Wang, Beck et al (2010). For related structures, see: Fun et al (2010); Li & Wu (2010); Xiao et al (2010); Praveen et al (2011). For standard bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…Amides are also used as ligands due to their excellent coordination abilities (Wu et al, 2008(Wu et al, , 2010 and for the therapy of thromboembolic disorder and effective anticoagulants for myocardial infarction and ischemic disease (Dorsch et al, 2002;Wang, Li & Li, 2010;Wang, Beck et al, 2010). Crystal structures of some acetamide derivatives, viz., 2-(4-bromophenyl)-N-(2-methoxyphenyl)acetamide (Xiao et al, 2010), N-benzyl-2-(2-bromophenyl)-2-(2-nitrophenoxy) acetamide (Li & Wu, 2010) and N-(3-chloro-4fluorophenyl)-2-(naphthalen-1-yl)acetamide (Praveen et al, 2011) have been reported. In view of the importance of amides, we report herein the crystal structure of the title compound.…”
Section: Data Collectionmentioning
confidence: 99%
“…For the coordination abilities of amides, see: Wu et al (2008Wu et al ( , 2010. For related structures, see: Akkurt et al (2010); Huang & Xu, (2006); Moreno-Fuquen et al (2011); Praveen et al (2011). For the crystal structure of another compound featuring C-HÁ Á ÁO contacts, see: Betz et al (2011).…”
Section: Related Literaturementioning
confidence: 99%